2021
DOI: 10.1136/svn-2020-000803
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment in anterior circulation stroke beyond 6.5 hours after onset or time last seen well: results from the MR CLEAN Registry

Abstract: BackgroundRandomised controlled trials with perfusion selection have shown benefit of endovascular treatment (EVT) for ischaemic stroke between 6 and 24 hours after symptom onset or time last seen well. However, outcomes after EVT in these late window patients without perfusion imaging are largely unknown. We assessed their characteristics and outcomes in routine clinical practice.MethodsThe Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands Registry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Our results show that treatment outcomes in nationwide routine clinical practice are well in keeping with the RCTs7 8 as well as the recent individual-level data AURORA (Analysis of Pooled Data from Randomized Studies of Thrombectomy More Than 6 Hours After Last Known Well) meta-analysis 19. The rate of functional independence in the AURORA meta-analysis EVT arm was 45.9%,19 while the corresponding rates in observational studies ranged from 24.5–62% 20–27. One recently published study on 53 702 EVTs in US clinical practice reported an equal proportion of late window EVTs (33%) to our nationwide material,28 while two other comparable studies presented lower proportions of late window treatments (10.7–11%) 20 22.…”
Section: Discussionsupporting
confidence: 83%
“…Our results show that treatment outcomes in nationwide routine clinical practice are well in keeping with the RCTs7 8 as well as the recent individual-level data AURORA (Analysis of Pooled Data from Randomized Studies of Thrombectomy More Than 6 Hours After Last Known Well) meta-analysis 19. The rate of functional independence in the AURORA meta-analysis EVT arm was 45.9%,19 while the corresponding rates in observational studies ranged from 24.5–62% 20–27. One recently published study on 53 702 EVTs in US clinical practice reported an equal proportion of late window EVTs (33%) to our nationwide material,28 while two other comparable studies presented lower proportions of late window treatments (10.7–11%) 20 22.…”
Section: Discussionsupporting
confidence: 83%
“…In a post hoc analysis of one registry,12 patients treated in the extended time window had similar rates of functional independence using CTP or NCCT (54.7% vs 60.6%). Several observational and registry studies11–17 35 showed similar results, but with the limitation of an indirect comparison between imaging modality, since their main objective was to compare the early versus extended time window or EVT versus best medical treatment.…”
Section: Discussionmentioning
confidence: 92%
“…It is unclear whether an approach to the extended window EVT that does not use ADVI would be equivalent to the current guidelines recommended strategy. Current evidence from cohort studies report conflicting results, with several studies suggesting superiority of ADVI,9 10 while others showed a similar proportion of functional independence without ADVI 9–17. Furthermore, no RCT compared these two approaches for patient selection during the extended time window in patients with anterior circulation LVO.…”
Section: Introductionmentioning
confidence: 99%
“…Previous observational studies assessing overall rates of functional independence (mRS ≤2) in the late EVT window have reported different results at 90-day follow-up, ranging from 20% to 64% using various pre-specified clinical and imaging patient selection criteria 8–11 18 20–23. Some of these investigations incorporated perfusion-based imaging with varying adherence to the DAWN and DEFUSE-3 eligibility criteria,18 20–23 while others used solely NCCT and CTA, but also varied in their selection criteria 8–11.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing RCTs are assessing whether treatment benefit with EVT is maintained in patients presenting beyond 6 hours of stroke onset when less restrictive clinical and imaging selection criteria are used 6 7. In the interim, functional and safety outcome data following EVT in the absence of CT perfusion or MR imaging in the late window is limited 8–11. Furthermore, while functional outcomes are highly time sensitive to EVT in the early (<6 hours) window, studies have reported a transition to a slower loss of effectiveness from EVT in the late window 12 13.…”
Section: Introductionmentioning
confidence: 99%